Descriptive Epidemiology of Upper Extremity Septic Arthritis in Children—Review of a Retrospective Multicenter Database. Issue 1 (31st January 2023) - Li, Ying; Sanborn, Ryan M.; Cook, Danielle; Baldwin, Keith D.; Beebe, Allan C.; Denning, Jaime R.; Goldstein, Rachel Y.; Janicki, Joseph A.; Johnson, Megan E.; Truong, Walter H.; Shore, Benjamin J.; ,
Abstract : Background: There is limited information on the presentation and management of upper extremity septic arthritis (UESA) in children. Our purpose was to report on the characteristics and short-term treatment outcomes of pediatric UESA from a multicenter database. Methods: Patients with UESA were identified from a multicenter retrospective musculoskeletal infection database. Demographics, laboratory tests, culture results, number of surgeries, and complications were collected. Results: Of 684 patients with septic arthritis (SA), 68 (10%) patients had UESA. Septic arthritis was most common in the elbow (53%), followed by the shoulder (41%) and wrist (4%). The median age at admission was 1.7 years [interquartile range(IQR, 0.8-8.0 y)] and 66% of the cohort was male. Blood cultures were collected in 65 (96%) patients with 23 (34%) positive results. Joint aspirate and/or tissue cultures were obtained in 66 (97%) patients with 49 (72%) positive results. Methicillin-sensitive Staphylococcus aureus (MSSA) was the most common causative organism overall, but Streptococcus was the most common pathogen in the shoulder. Sixty-six (97%) patients underwent irrigation and debridement, with 5 (7%) patients requiring 2 surgeries and 1 patient (1%) requiring 3 surgeries. The median length of stay was 4.9 days (IQR, 4.0-6.3 d). Thirty-one (46%) children had adjacent musculoskeletal infections and/or persistent bacteremia. No patients experienced venous thromboembolism, and 4 patients with associated osteomyelitis experienced a musculoskeletal complication (3 avascular necrosis, 1 pathologic fracture). One child had re-admission and 3 children with associated osteomyelitis had a recurrence of UESA. Comparison between elbow and shoulder locations showed that children with septic arthritis of the shoulder were younger (4.6 vs. 1.0 y, P =0.001), and there was a difference in minimum platelet count (280 vs. 358 ×10 9 cells/L, P =0.02). Conclusions: UESA comprises 10% of cases of septic arthritis in children. The elbow is the most common location. Shoulder septic arthritis affects younger children. MSSA is the most common causative organism in UESA, but Streptococcus is common in shoulder septic arthritis. Irrigation and debridement result in excellent short-term outcomes with a low complication rate. Re-admissions and repeat surgical interventions are rare. Level of Evidence: Level IV, prognostic.